TANTANGAN GURU PENDIDIKAN AGAMA ISLAM DI ERA 4.0 - Akhmad Riadi (AZKIYA, 2019)
The teacher's role is very central as the direct implementer of the curriculum designed by the Government, so teachers must continue to innovate and improve the quality of human resources in line with the development of Information and Technology. In the era of 4.0 Islamic Religious Education teachers must have competencies, there are at least 4 competencies that must be possessed, Teachers must be able to conduct Comprehensive Assessment, teachers must have 21st century competencies namely mastery of Information Technology, Teachers Must be able to present Modules in accordance with Student Passions, and Teachers must able to perform Innovative Autentic Learning. In addition to these competencies, teachers must also pay attention to the challenges in areas 4.0 such as teaching in communities that have diverse cultures with multi-language competencies, teaching for active learning, teaching and accountability, so that the challenges of educational development can be passed by teachers with human resources who are always innovating